Cortical folding patterns are associated with impulsivity in healthy young adults - Hirjak, Dusan; Thomann, Anne K.; Wolf, Robert Christian; Jeung, Haang; Thomann, Philipp (Brain imaging and behavior, 2017)
Impulsivity is associated with distinct mental disorders but is also considered as a personality trait exhibited by healthy individuals. Current studies suggest that early stressful life events might cause higher impulsivity in the adulthood. Morphological features, which reflect early brain development, could provide valuable information regarding the origin of impulsive behavior. However, none of the previous MRI studies employed a methodology specifically designed to investigate the relationship between impulsivity and markers of brain development. In this regard, we aimed to investigate the relationship between cortical folding and the three distinct factors of impulsivity (attention, motor, and non-planning) in young healthy adults. Fifty-four right-handed healthy individuals were recruited for the study and underwent magnetic resonance imaging (MRI) at 3 Tesla. A surface-based analysis was used to calculate a local gyrification index (LGI). Impulsivity was examined by the Barratt Impulsiveness Scale (BIS-11) and related to LGI. Associations between LGI and BIS-11 scores were assessed using within-group correlations (p < 0.05, “cluster-wise probability” [CWP] corr.). BIS subscores were positively correlated with cortical folding in several distinct areas: Total and attention scores were positively correlated with LGI in the left postcentral gyrus, cingulate gyrus, precentral gyrus, pars opercularis of the inferior frontal gyrus, right middle temporal gyrus, superior parietal gyrus, pericalcarine gyrus, and lateral occipital gyrus (each p < 0.05 CWP corr.). BIS motor score was positively correlated with LGI in the left superior temporal, lingual and supramarginal gyrus (each p < 0.05 CWP corr.). BIS non-planning score showed a positive correlation with LGI in the pars opercularis of the right inferior frontal gyrus and the left middle temporal, precentral and superior parietal gyrus (each p < 0.05 CWP corr.). Furthermore, we found gender-specific differences in BIS-11-LGI-correlation in the middle and inferior frontal gyrus. Our findings illustrate the advantages of cortical folding as a marker of early brain development when investigating structural brain correlates of impulsivity in young adulthood. Further, they lend additional support to the notion that alterations in early neurodevelopment comprising fronto-temporo-parietal regions might give rise to higher impulsivity in healthy individuals.